(untitled) (Indonesian Court and Justice Review, 2024)
Cybercrime presents a significant challenge to traditional legal frameworks, particularly classical criminal law principles such as legality (nullum crimen sine lege), culpability, and proportionality. This study explores the extent to which these foundational principles remain relevant and applicable in Indonesia’s approach to cybercrime. Drawing upon legal doctrinal analysis and statutory review, as well as selected court decisions involving cyber defamation, hacking, and data theft, the research critically assesses how classical principles are being interpreted and adapted in digital contexts. The findings reveal a complex legal landscape: while the principles of legality and culpability continue to serve as cornerstones of criminal justice, ambiguities in cybercrime legislation and expansive interpretations by courts may undermine legal predictability and individual protections. For instance, the broad language of the Electronic Information and Transactions (EIT) Law often clashes with the requirement of specificity in criminal law. This study argues that a careful recalibration of classical doctrines is needed—one that maintains legal safeguards while allowing flexibility in addressing evolving digital harms. The novelty of the research lies in its re-examination of enduring criminal law theories in light of contemporary challenges, offering doctrinal and policy insights for reform. As cybercrime grows more sophisticated, ensuring that criminal law remains principled yet adaptable is both a legal and ethical imperative.